Particle production as a function of charged-particle flattenicity in pp collisions at √sp=13TeV - Acharya, S.; Adamova, D.; Agarwal, A.; Rinella, G. Aglieri; Aglietta, L.; Agnello, M.; Agrawal, N.; Ahammed, Z.; Ahmad, S.; Ahn, S. U.; Ahuja, I.; Akindinov, A.; et al. (AMER PHYSICAL SOC, 2025)
This paper reports the first measurement of the transverse momentum (p(T)) spectra of primary charged pions, kaons, (anti)protons, and unidentified particles as a function of the charged-particle flattenicity in pp collisions at root s = 13 TeV. Flattenicity is a novel event shape observable that is measured in the pseudorapidity intervals covered by the V0 detector, 2.8 < eta < 5.1 and -3.7 < eta < -1.7. According to QCD-inspired phenomenological models, it shows sensitivity to multiparton interactions and is less affected by biases toward larger pT due to local multiplicity fluctuations in the V0 acceptance than multiplicity. The analysis is performed in minimum-bias (MB) as well as in high-multiplicity events up to p(T) = 20 GeV/c. The event selection requires at least one charged particle produced in the pseudorapidity interval |eta| < 1. The measured p(T) distributions, average p(T), kaon-to-pion and proton-to-pion particle ratios, presented in this paper, are compared to model calculations using PYTHIA 8 based on color strings and EPOS LHC. The modification of the p(T)-spectral shapes in low-flattenicity events that have large event activity with respect to those measured in MB events develops a pronounced peak at intermediate p(T) ( 2 < p(T) < 8 GeV/c), and approaches the vicinity of unity at higher p(T). The results are qualitatively described by PYTHIA, and they show different behavior than those measured as a function of chargedparticle multiplicity based on the V0M estimator.
Keywords: PROTON-PROTON COLLISIONS; PB-PB COLLISIONS; MULTIPLICITY DEPENDENCE; LONG-RANGE; TRANSVERSE SPHEROCITY; ANGULAR-CORRELATIONS; HADRON-PRODUCTION; CROSS-SECTIONS; JET PRODUCTION; COLLECTIVITY; Astronomy & Astrophysics; Physics